Biodiversity and seasonal distribution of benthic diatom assemblages as an indicator of water quality of small karstic river in Bosnia and Herzegovina - Dedić, Anita (Array, 2021)
The aims of this paper were to describe seasonal changes in the qualitative and quantitative composition of diatom taxa and the potential application of benthic diatoms for ecological status evaluation. Diatom indices (IPS and TI) were calculated from data from three different locations along a longitudinal profile of the Bunica, a small karstic river in Bosnia and Herzegovina. A total of 147 taxa were recorded in 12 samples. The most common taxa were Meridion circulare (Greville) C.Agardh and Ulnaria ulna (Nitzsch) Compère. Physical and chemical analyses showed low concentrations of nutrients, good oxygenation, typical pH for carbonate bed/origin and generally oligotrophic conditions and high ecological status. All sites had similar physico-chemical conditions and there were only few seasonal differences. Ordination of the diatom data showed that samples showed neither longitudinal nor seasonal patterns. Median value for IPS (16.8) and for TI (7.3) can be possible ""expected"" values for ecological status assessment for small karstic rivers in the Mediterranean region. We propose the use of the phytobenthos Intercalibration Common Metric (pICM - an index that combines the IPS and TI) as a national metric for countries developing WFD diatom methods at a late stage. One situation is described, and a solution, which is potentially transferable to other locations in Bosnia and Herzegovina and also to other countries facing similar challenges.